Development of Multiple-Input Power Management Circuit for Piezoelectric Harvester / Mohd Sofwan Mohd Resali and Hanim Salleh - Mohd Resali, Mohd Sofwan; Salleh, Hanim (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
This paper discusses the multisource input from the piezoelectric (PZT) generators to the power management circuit (PMC) of the energy harvesting system. It discusses the structure of the PMC starting from the AC-DC full bridge rectifier circuit and the structure of the storage circuit of the power management circuit itself. The AC-DC rectifier circuit was compared with separated AC-DC rectifier, series and parallel connection to choose the best performance output and structure. The storage circuit was also compared between traditional method and switch circuit. This paper also describes the designing circuit of the PMC from the software and fabricating it to PCB board circuit. The PMC was tested by connecting 4 input PZT generators which were harvested from the vibration and connected to the application electronic load circuit such as microcontroller and sensors to complete it as an energy harvesting vibration based system. The performance test was conducted by testing it in a laboratory and field test at one of the cooling fan power stations which provides continuous vibration from the motor. Two methods of testing were conducted to measure the performance of the PMC which were laboratory test and field test at the vibrating motor of cooling fan in power station. The 70% of the efficiency was recorded for both laboratory test and field test from the PMC. The output power of the PMC is 1.94mW and the input power is from the multisource input PZT. Author also makes a comparison between the performances of the PMC with other previous designs.